Development of Gluten-Free Coated Chicken Liver, Examination of the Effects of Spices and Cooking Methods on Product Quality Characteristics and Heterocyclic Aromatic Amine (HCA) Compounds - Berna Capan; Gulen Yildiz Turp (Applied Sciences)
The objectives of this study were to develop a coated gluten-free chicken liver product that could be consumed by a wide range of consumer groups and to investigate the quality characteristics and heterocyclic aromatic amine (HCA) compounds. The effects of three different formulations (thyme, turmeric, and control) and two different cooking methods (deep-frying and oven cooking) on the physical, chemical, microbiological, and sensorial characteristics and HCA compounds of samples, which were stored at −20 °C for 60 days, were investigated. TBARS values were lower in the oven-cooked samples than in the deep-fried samples at the end of the storage, with turmeric proving most effective (p < 0.05). TMAB and total HCA were lower in thyme and turmeric-added samples than in the control samples (p < 0.05). The total HCA content of the deep-fried and oven-cooked samples decreased by 14.42% and 13.20% with the addition of thyme and by 18.75% and 23.35% with the addition of turmeric, respectively. The oven-cooked sample with turmeric was stored for 60 days without any significant changes in the color, flavor, and overall acceptance according to the beginning of the storage (p > 0.05). In conclusion, gluten-free oven-cooked turmeric-added coated chicken liver can be a healthy food alternative in the market.